IN MEMORIAM DOCTOR BOTJAH PRIJANTO - Mien A. Rifai (REINWARDTIA, 1970)
With the premature death of Dr.Botjah Prijanto on 29 April 1969,Indonesian botany has lost one of its few potential cadres.That the progress of the development of botany in Indonesia will be seriously impeded by his untimely death will be evident from the fact that Dr. Prijanto was the first and only Indonesian palynologist.Moreover he was one of the very few Indonesian qualified taxonomic botanists to obtain and complete their academic training in well established botanical institutions abroad.